Penyuluhan Kesehatan Reproduksi Pada Wanita Menopause - Ela Rohaeni; Iis; Ira Lutfiatunnabil; Syalsa Nurhaliza (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2024)
Menopause is the period when menstruation stops which occurs in women aged 48 to 55 years. Menopause is a phase where women do not experience menstruation. It is hoped that the benefits and objectives of this counseling will be useful for improving and increasing knowledge about Reproductive Health in Menopausal Women. Menopause is a phase where women do not experience menstruation. Often women face menopause with anxiety and fear because they are entering old age and are no longer able to bear children. The method used in this program is to provide health education through counseling about Reproductive Health in Menopausal Women. Based on the results of the Self-Awareness Survey, there are several problems, namely the large number of teenagers who consume unhealthy food, teenagers who do not know about reproductive health, the lack of knowledge of pregnant women and mothers with toddlers regarding the contents of MCH books and the lack of knowledge of menopausal women in caring for reproductive health. The priority problem is the lack of knowledge of menopausal women in caring for reproductive health. With 110 people interviewed, there were 101 menopausal women who said they did not know about caring for reproductive health. From the SMD results, we found the problem of low levels of knowledge of reproductive health in menopausal women. To overcome this, we made one effort to provide education regarding reproductive health in menopausal women. After the counseling was carried out, participants looked enthusiastic about the counseling material presented and were able to practice how to care for reproductive health.